“A Man With(out) a Face”: Stigma and Power in Cecile Pineda’s Face - Fatma Eren (European Journal of American Studies)
This study analyzes the social perception and changing nature of human relations with facial disfigurement on the example of the main character in Cecile Pineda’s Face (1985). Losing his face in a tragic accident, Helio Cara in Face is stigmatized and experiences social aversion from the majority who deem themselves to be “normal.” With his disfigured face, he is considered “disqualified” to continue his former life and is expected to act in accordance with his stigmatized identity and yield to the effects of power that determine his everyday relations. In other words, Cara’s facial deformity determines his stigmatized social position as his living routine is restructured within the dynamics of the culture of aversion and power. A closer look, however, reveals that as a stigmatized subject, Helio Cara is actually a victim of a mentality conditioned by a set of expectations that are transformed into “ideals” and “standards” to which people should conform. In this respect, it is the stigmatized role imposed on him by the power relations rather than his disfigured face which negatively affects Cara’s physical and psychological health and causes him to be targeted by society. Cecile Pineda, Face, aversion, power, stigma